Health care in reproductive planning: attitudes and nurses' practices - Maryla Pinto Almeida; Mônica Cecília Pimentel de Melo; Lucineide Santos Silva; Ana Dulce Batista dos Santos (Universidade Federal de Santa Maria, 2016)
Aim: to analyze the attention on health care employed by nurses at the reproductive planning, by family health teams from Juazeiro, Bahia. Method: qualitative, exploratory and descriptive study in which was used semi-structured interview with eight nurses from five Family Health Units, with the largest number of women at childbearing age. Results: scarcity and irregularity in the supply of the methods emerged, compromising the effectiveness and quality of reproductive planning. The instability of the educational activities pointed at women and/or couples uninformed about the use and benefits of these methods, revealing self-medication and search in pharmacies. Conclusions: the construction of an attention on health care that acts in the premises of the quality, effectiveness and equity can contribute to a more autonomous nursing that is also consistent with the needs of the population in reproductive planning